Drop jump asymmetry is associated with reduced sprint and change-of-direction speed performance in adult female soccer players - Bishop, C.; Turner, A.; Maloney, S.; Lake, J.; Loturco, I.; Bromley, T.; Read, P. (Sports, 2019)
Studies that examine the effects of inter-limb asymmetry on measures of physical performance are scarce, especially in adult female populations. The aim of the present study was to establish the relationship between inter-limb asymmetry and speed and change-of-direction speed (CODS) in adult female soccer players. Sixteen adult players performed a preseason test battery consisting of unilateral countermovement jump (CMJ), unilateral drop jump (DJ), 10 m, 30 m, and 505 CODS tests. Inter-limb asymmetry was calculated using a standard percentage difference equation for jump and CODS tests, and Pearson`s r correlations were used to establish a relationship between asymmetry and physical performance as well as asymmetry scores themselves across tests. Jump-height asymmetry from the CMJ (8.65%) and DJ (9.16%) tests were significantly greater (p < 0.05) than asymmetry during the 505 test (2.39%). CMJ-height asymmetry showed no association with speed or CODS. However, DJ asymmetries were significantly associated with slower 10 m (r = 0.52; p < 0.05), 30 m (r = 0.58; p < 0.05), and 505 (r = 0.52-0.66; p < 0.05) performance. No significant relationships were present between asymmetry scores across tests. These findings suggest that the DJ is a useful test for detecting existent between-limb asymmetry that might in turn be detrimental to speed and CODS performance. Furthermore, the lack of relationships present between different asymmetry scores indicates the individual nature of asymmetry and precludes the use of a single test for the assessment of inter-limb differences